2010
DOI: 10.1073/pnas.1016233107
|View full text |Cite
|
Sign up to set email alerts
|

Target-seeking antifibrotic compound enhances wound healing and suppresses scar formation in mice

Abstract: Permanent scars form upon healing of tissue injuries such as those caused by ischemia (myocardial infarction, stroke), trauma, surgery, and inflammation. Current options in reducing scar formation are limited to local intervention. We have designed a systemically administered, target-seeking biotherapeutic for scar prevention. It consists of a vascular targeting peptide that specifically recognizes angiogenic blood vessels and extravasates into sites of injury, fused with a therapeutic molecule, decorin. Decor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(184 citation statements)
references
References 55 publications
2
182
0
Order By: Relevance
“…On the one hand, biological augmentations of IGF-1 can improve tendon healing, and the absence of IGF-1 leads to an inferior repair response. On the other hand, reductions in levels of TGFβ have been associated with reduced scar formation (111).…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…On the one hand, biological augmentations of IGF-1 can improve tendon healing, and the absence of IGF-1 leads to an inferior repair response. On the other hand, reductions in levels of TGFβ have been associated with reduced scar formation (111).…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…Animal models have shown that absence of decorin exacerbates fibrosis (13, 247, 316). Moreover, interesting data suggest that decorin itself could be a beneficial Review antifibrotic therapeutic alternative (156,186,402). A suggested antifibrotic mechanism of decorin deals, at least partially, with the inactivation of TGF-␤ signaling (14), impairing myofibroblastic differentiation in liver fibrosis models (14).…”
Section: Proteoglycansmentioning
confidence: 99%
“…Most importantly, loss of COL7A1 led to increased production of TGF-β1, which stimulates synthesis of extracellular matrix and scarring in RDEB (43)(44)(45). TGF-β signaling and tissue stiffness drive myofibroblast differentiation (46)(47)(48).…”
Section: Figurementioning
confidence: 99%